2022
DOI: 10.3390/brainsci12050563
|View full text |Cite
|
Sign up to set email alerts
|

Literacy Acquisition Trajectories in Bilingual Language Minority Children and Monolingual Peers with Similar or Different SES: A Three-Year Longitudinal Study

Abstract: Bilingualism and socio-economic status (SES) differentially affect linguistic and cognitive development. However, less evidence has been collected regarding their impact on literacy trajectories. The present longitudinal study evaluated the literacy development of language minority bilingual children (LMBC) and monolingual peers with different SES. A group of LMBC with low-SES (n = 18) and monolingual peers with low (n = 18) or high (n = 14) SES were followed from 2nd to 5th grade through a set of tasks assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Therefore, we interpreted that the reading test was valid to measure students' reading comprehension achievement in Myanmar. The reason may be that all types of questions in the reading test are based on the prescribed reading text and its example questions for grade-9 students in Myanmar [56]. The confirmation of measurement invariance across the experimental and control groups indicates that the pre-/post-tests used in this study are equally valid and reliable for assessing reading comprehension achievement in both groups.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Therefore, we interpreted that the reading test was valid to measure students' reading comprehension achievement in Myanmar. The reason may be that all types of questions in the reading test are based on the prescribed reading text and its example questions for grade-9 students in Myanmar [56]. The confirmation of measurement invariance across the experimental and control groups indicates that the pre-/post-tests used in this study are equally valid and reliable for assessing reading comprehension achievement in both groups.…”
Section: Discussionmentioning
confidence: 62%
“…Reading is an essential skill for students that plays a vital role in the sustainability of their academic and professional development [56]. Therefore, there have been studies investigating the effectiveness of instructional strategies [57][58][59][60] on students' reading comprehension.…”
Section: Previous Findings On Reading Comprehension Achievementmentioning
confidence: 99%
“…Previous studies reported a negative impact of low SES on vocabulary knowledge and vocabulary growth [51,52], early literacy [53], early numeracy [54,55], and listening/ reading comprehension skills [56,57]. Also, disparities in children's well-being and mental health concerning SES emerged [58].…”
Section: The Role Of Socioeconomic Status On Children's Early Literac...mentioning
confidence: 98%
“…In addition, greater economic and social freedom might have repercussions on how resources shape experience and, therefore, on subjective experience (Kraus et al, 2012). We already know from the literature that SES has an impact on children's linguistic skills: for example, vocabulary knowledge and vocabulary growth, syntax and language learning process (Hoff, 2003(Hoff, , 2006Levine et al, 2020), as well as literacy skills (Bonifacci et al, 2022;Bonifacci et al, 2020) are known to be negatively affected by lower levels of SES.…”
Section: Introductionmentioning
confidence: 99%